San Francisco area Methodist Youth Assembly - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group photograph of the San Francisco area Methodist Youth Assembly. The building in the background, potentially a Methodist church, for the group portrait has visible details of stained glass windows on the left side of the photograph. A majority of the assembly members have ribbons attached to their clothing. The Sequoia and Chico members identify themselves with signs. Some members to the right of the group are wearing scarves and hold a banner with a picture of the planet. The printing on the banner is illegible.